Meningkatkan Kemampuan Membaca Huruf Hijaiyah Bersambung dengan Metode Talaqqi pada Anak Gangguan Spektrum Autisme - Sari, Ratna; Armaini, Armaini (Jurnal Penelitian Pendidikan Khusus, 2022)
This research is based on the problems that the authors found in disability and parent help. In this study, the researcher describes a student (X) who has an autism spectrum disorder, aged approximately 7 years. Student (X) is able to read hijaiyah letters from alif to yes, but is constrained when reading continuous hijaiyah letters. The purpose of this study for students (X) was to improve the ability to read hijaiyah letters using the talaqqi method in children with autism spectrum disorders. This study uses a single subject research (SSR) method with an A-B-A design. In Basaline A1 (initial condition) observations were made four times which obtained percentage results as much as 30% to 50%, at the time of intervention using the talaqqi method, nine observations were made and obtained percentage results of 52.78% to 100%, while in baseline A2 after no further treatment was given where three observations were made and obtained a stable percentage result from the beginning to the end of 100%.Based on the results of this study, it can be concluded that the ability to read hijaiyah letters using the talaqqi method in children with autism spectrum disorders and not using the talaqqi method has increased and has stabilized. Thus the talaqqi method is able to improve the ability to read hijaiyah letters in children with autism spectrum disorders.